Exploring Charismatic Leadership as a Strategy for Improving Teacher Performance: A Systematic Literature Review - Mukhlisin, Muhammad Khoirul; Maisyaroh; Sunandar, Asep (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to examine the role of charismatic leadership as an effective strategy in improving teacher performance through a systematic review of the latest literature. Charismatic leadership has long been considered a potential strategy for improving teacher performance in educational contexts. This study aims to systematically review the literature on charismatic leadership using a Systematic Literature Review (SLR) approach to identify its antecedents, implications, and limitations. The results of the review indicate that certain personality traits, such as agreeableness, persistence, and cognitive ability, are consistent predictors of idealized influence, while extroversion is more dominant in influencing inspirational motivation. Empirical evidence also supports that charismatic leadership can increase teachers' extra-role behaviors (OCB), improve task performance, and positively impact performance outcomes at both the group and educational organization levels. These findings confirm the important role of charismatic leadership in professional and service contexts in education, and its implications for leadership selection and training practices. However, the results also reveal significant limitations, including heterogeneity in definitions and measurement instruments, the predominance of cross-sectional research designs with self-reports, and the lack of a multilevel approach to analysis. Therefore, further research is needed to adopt longitudinal, experimental, and multilevel designs to achieve a more comprehensive, valid, and applicable understanding of the role of charismatic leadership in education. The results of this study provide a theoretical and practical basis for leadership development and the design of training programs for teachers.